Asian views on America's role in Asia the future of the rebalance : strategic recommendations for the incoming U.S. President on foreign policy towards Asia (The Asia Foundation, 2016)
The 2016 U.S. elections have emerged as a signal moment in the evolution of America's engagement with the world and its commitment to the international order that it was instrumental in building. At the same time, with 60 percent of the world's population and some of the world's fastest-growing economies, Asia's rising strategic importance cannot be denied. We have summarized here just a handful of the issues that emerged during the three Asian subregional meetings in Bangkok, Colombo, and Seoul. What follows is a set of specific recommendations that we, the project's three Asian chairs, feel to be the most important. In addition to these issues and recommendations, the chapters of this report delve in deeper detail into the U.S. foreign-policy concerns most important to all three subregions. If the 45th president of the United States and the Congress that assumes office in January 2017 adopt these recommendations, we believe that U.S. relations with Asia as a whole will improve and prosper.